Activation and detoxification metabolism of urban air pollutants 2-nitrobenzanthrone and carcinogenic 3-nitrobenzanthrone by rat and mouse hepatic microsomes - Stiborova, Marie; Cechova, Tereza; Borek-Dohalska, Lucie; Moserova, Michaela; Frei, Eva; Schmeiser, Heinz H; Paca, Jan; Arlt, Volker M (Neuro endocrinology letters, 2012)
OBJECTIVES: 2-Nitrobenzanthrone (2-NBA) has recently been detected in ambient air particulate matter. Its isomer 3-nitrobenzanthrone (3-NBA) is a potent mutagen and suspected human carcinogen identified in diesel exhaust. Understanding which enzymes are involved in metabolism of these toxicants is important in the assessment of individual susceptibility. Here, metabolism of 2-NBA and 3-NBA by rat and mouse hepatic microsomes containing cytochromes P450 (CYPs), their reductase (NADPH:CYP reductase), and NADH:cytochrome b5 reductase was investigated under anaerobic and aerobic conditions. In addition, using the same microsomal systems, 2-NBA and 3-NBA were evaluated to be enzymatically activated under anaerobic conditions to species generating 2-NBA- and 3-NBA-derived DNA adducts. METHODS: High performance liquid chromatography (HPLC) with ultraviolet (UV) detection was employed for the separation and characterization of 2-NBA and 3-NBA metabolites formed by hepatic microsomes of rats and mice under the anaerobic and aerobic conditions. Microsomal systems isolated from the liver of the control (untreated) rats and rats pretreated with Sudan I, β-naphthoflavone (β-NF), phenobarbital (PB), ethanol and pregnenolon 16α-carbonitrile (PCN), the inducers of cytochromes P450 (CYP) 1A1, 1A1/2, 2B, 2E1 and 3A, respectively, were used in this study. Microsomes of mouse models, a control mouse line (wild-type, WT) and Hepatic Cytochrome P450 Reductase Null (HRN) mice with deleted gene of NADPH:CYP reductase in the liver, thus absenting this enzyme in their livers, were also employed. To detect and quantify the 2-NBA- and 3-NBA-derived DNA adducts, the 32P postlabeling technique was used. RESULTS: Both reductive metabolite of 3-NBA, 3-aminobenzanthrone (3-ABA), found to be formed predominantly under the anaerobic conditions, and two 3-NBA oxidative metabolites, whose structures have not yet been investigated, were formed by several microsomal systems used in the study. Whereas a 3-NBA reductive metabolite, 3-ABA, was found only in the microsomal systems of control rats, the rats treated with β-NF and PB, and microsomes of WT and HRN mice, all hepatic microsomes tested in the study were capable of activating this carcinogen under the reductive conditions to form DNA adducts. A stability of a reactive intermediate of 3-NBA, N-hydroxy-3-aminobenzanthrone that is formed during 3-NBA reduction to 3-ABA, to form nitrenium (and/or carbenium) ions binding to DNA in individual microsomes as well as binding of these ions to proteins of these microsomes, might be the reasons explaining this phenomenon. In contrast to 3-NBA, its isomer 2-NBA was not metabolized by any of the used enzymatic systems both under the anaerobic and aerobic conditions. Likewise, no DNA adducts were detectable after reaction of 2-NBA in these systems with DNA. CONCLUSIONS: The results found in this study, the first report on the metabolism of 2-NBA and 3-NBA by rat and mouse hepatic microsomes demonstrate that 3-NBA, in contrast to 2-NBA, is reductively activated to form 3-NBA-derived DNA adducts by these enzymatic systems. NADPH:CYP reductase can be responsible for formation of these DNA adducts in rat livers, while NADH:cytochrome b5 reductase can contribute to this process in livers of HRN mice.
Keywords: benz(a)anthraceny; Animals; Mice, Inbred Strains; NADPH-Ferrihemoprotein Reductase; Urban Health; výfukové emise vozidel; Rats, Wistar; inbrední kmeny myší; Substrate Specificity; Mice, Knockout; myši knockoutované; NADPH-cytochrom c-reduktasa; adukty DNA; Mice; Vehicle Emissions; Inactivation, Metabolic; cytochrom-B(5)-reduktasa; Carcinogens; myši; jaterní mikrozomy; metabolická inaktivace; Models, Animal; aerobióza; Male; Air Pollutants; karcinogeny; zdraví ve městech; DNA Adducts; systém (enzymů) cytochromů P-450; Microsomes, Liver; Aerobiosis; krysa rodu Rattus; Cytochrome-B(5) Reductase; Benz(a)Anthracenes; Anaerobiosis; zvířata; mužské pohlaví; anaerobióza; substrátová specifita; látky znečišťující vzduch; Rats; Cytochrome P-450 Enzyme System; modely u zvířat; potkani Wistar